IMPLEMENTATION OF THE GOVERNOR REGULATION OF THE SPECIAL CAPITAL REGION OF JAKARTA PROVINCE NUMBER 68 OF 2021 CONCERNING THE “RESTRICTION OF PRIVATE MOTOR VEHICLES” IN SOUTH JAKARTA - Yudoyono, Yeremia Adrian; Yuniningsih, Tri; Hidayati, Rizky; Arjun Syarifah, Sekar Arum; Myeong, Seunghwan (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2026)
Traffic congestion remains a major issue in DKI Jakarta, particularly in South Jakarta, which has a high level of mobility and a large volume of private vehicles. The Provincial Government of DKI Jakarta has issued Governor Regulation Number 68 of 2021 to restrict private motor vehicles through traffic management measures, the implementation of the odd-even license plate system, traffic engineering, and parking management. However, its implementation has not been fully effective in reducing congestion on strategic road segments. This study analyzes the implementation of the policy and its inhibiting factors using a descriptive qualitative approach through in-depth interviews, field observations, and document analysis with officials from the South Jakarta Sub-Department of  Transportation as informants. The analysis focuses on policy communication, resource availability, implementers’ attitudes, and bureaucratic structure. The findings indicate that although the policy has been implemented, its effectiveness remains limited due to low public compliance, inadequate supporting facilities, suboptimal inter-agency coordination, and the dominance of private vehicles. Therefore, this study recommends strengthening policy evaluation, ensuring consistent supervision, and aligning vehicle restriction policies with improvements in the quality and attractiveness of public transportation as the main strategy to reduce congestion in South Jakarta.